2007
DOI: 10.1001/archopht.125.5.661
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Vitamin D and Age-Related Macular Degeneration in the Third National Health and Nutrition Examination Survey, 1988 Through 1994

Abstract: To evaluate the associations between levels of vitamin D (25-hydroxyvitamin D) in serum and prevalent age-related macular degeneration (AMD). Methods and Design: Cross-sectional associations of serum vitamin D and early and advanced AMD, assessed from nonmydriatic fundus photographs, were evaluated in the third National Health and Nutrition Examination Survey, a multistage nationally representative probability sample of noninstitutionalized individuals (N=7752; 11% with AMD). Results: Levels of serum vitamin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
135
2
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(145 citation statements)
references
References 62 publications
4
135
2
4
Order By: Relevance
“…This result corroborates with the observation that calcitriol may protect against age-related macular degeneration in humans. 31 The influence of vitamin D on the neurofeedback components could therefore explain in part the involvement of vitamin D in postural and gait control. Nevertheless, we found an association between STV and serum vitamin D status in spite of the adjustment on lower limb proprioception, standing postural sways, and visual acuity.…”
Section: Resultsmentioning
confidence: 99%
“…This result corroborates with the observation that calcitriol may protect against age-related macular degeneration in humans. 31 The influence of vitamin D on the neurofeedback components could therefore explain in part the involvement of vitamin D in postural and gait control. Nevertheless, we found an association between STV and serum vitamin D status in spite of the adjustment on lower limb proprioception, standing postural sways, and visual acuity.…”
Section: Resultsmentioning
confidence: 99%
“…The specific effect that vitamin D has on AMD was investigated because of the anti-inflammatory properties found in vitamin D. The results from the National Health and Nutrition Examination Survey study showed an association between the plasma levels of vitamin D and early AMD, with no association reported for advanced AMD [49]. [51].…”
Section: Vitamin Dmentioning
confidence: 99%
“…There have been only a few observational studies regarding the role of vitamin D in ameliorating AMD risk [134] (Figures 40-42 (Figure 40). There was no effect of serum levels of vitamin D on the appearance of pigment abnormalities or advanced AMD (Figure 40).…”
Section: Vitamin Dmentioning
confidence: 99%